Epidermoid Cyst in the Bitch Mammary Gland - Almeida Viscone, Érica; Ribeiro Nakagaki, Karen Yumi; Wronski, Julia Gabriela; Meira Nunes, Maira; Dantas Cassali, Geovanni (Acta Scientiae Veterinariae, 2024)
Background: An epidermoid cyst is a result of the growth of epidermal elements in the dermis. It might occur anywhere in the body, both in humans and animals. A few case reports have demonstrated these cysts in the human mammary gland, but in the bitch mammary gland, it is not a reality. The exact pathogenesis of mammary epidermoid cysts remains unknown. At first, this lesion is considered benign; however, a malignant transformation can occur leading to squamous cell carcinoma. This paper reports the 1st occurrence of epidermoid cyst in the bitch mammary gland. Case: A mammary chain with the inguinal lymph node was received from a 12-year-old bitch mixed breed. Macroscopically, all glands had tumors, ranging from 0.7 cm to 3.5 cm along their longest axis. At the caudal thoracic gland (M2), a well-defined lump, measuring 2.0 x 1.8 x 1.4 cm, soft to firm consistency, with intact skin, was noted. After sectioning, a cystic cavity measuring 1.5 x 1.2 cm filled with a white-yellow caseous material, was observed. Samples were collected and submitted for routine histopathology. Microscopic analysis revealed tissue from the mammary gland covered by intact epithelium. Between the mammary glands, a large cystic cavity was observed, filled with lamellated keratin, acantholytic keratinocytes, neutrophils, foamy macrophages, and cellular debris. A thick layer of stratified squamous epithelium covered the cyst with some points of rupture infiltrated by neutrophils, macrophages, lymphocytes, and plasma cells, also with keratin released to the mammary stroma. The adjacent glands showed a few spots of ductal ectasia. Malignant criteria were absent. Discussion: Epidermoid cysts, commonly, arise from the infundibular portion of the hair follicle, are lined by squamous epithelium with a granular layer, and filled with laminated keratin. In humans, this entity might be found in the breast and could be a challenge to differentiate them from other benign and malignant conditions. As these lesions grow slowly through the accumulation of keratin over time, it can lead to complications by spontaneous rupture, release of no absorbable keratin that acts like an irritant material, stimulating secondary foreign body reactions, granulomatous reactions, or abscess formation. The inflammatory reaction results in local swelling and pain. The exact pathogenesis of mammary epidermoid cysts remains unknown; however, a few proposals exist: (a) congenital, arising from cell nests remaining from cells such as the embryonal mammary ridge; (b) obstruction of the hair follicle in the mammary dermis; (c) damage to the epidermis which gets implanted deep within the breast tissue and may occur in any type of trauma and/or previous procedures; (d) cystic ectasia of the infundibulum of hair follicles; and (e) squamous metaplasia of normal columnar cells within a dilated duct in fibroadenoma or fibrocystic change. The final diagnosis in this case was established by histopathological examination stained with hematoxylin and eosin. Epidermoid cyst is a benign lesion that occurs anywhere in the body, they are more common on the face, trunk, neck, extremities, scalp and has been described in the human mammary gland. In the authors’ assessment, this is the 1st description of epidermoid cyst in the bitch mammary gland. Although it is a very rare entity, pathologists need to be aware and should be considered as a differential diagnosis during mammary gland examination. Keywords: canine, squamous cells, epidermal inclusion, ductal metaplasia, laminated keratin, morphology.